Implementation of Elderly School Bagja Lahir Batin in Raja Manggala Kulon, Cipatat, West Bandung, West Java Province - Rizky Erwanto; Dwi Endah Kurniasih; Rachmat Ari Kusumanto; Budi Raharja (Journal of Health Community Service, 2023)
An increase in the number of the elderly population becomes a problem if the elderly experience a decline in health which has an impact on increasing healthcare costs, increasing disability rates, decreasing income, lack of social support and an environment that is less friendly to the elderly. BAZNAS (National Amil Zakat Agency) of West Java Province in collaboration with Yayasan Indonesia Ramah Lansia and the West Bandung District Government of West Java Province, is committed to providing services to the elderly and providing education to the public to care for the elderly, namely the Nya'ah Ka Kolot (care for the elderly) program. One of the activities of the Nya'ah Ka Kolot extensive program to contribute to improving the quality of life of the elderly is an informal school for the elderly called "Sekolah Lansia Bagja Lahir Batin". This activity is carried out once a month for ten months. Elderly who attends elderly schools experience an increase in knowledge and skills regarding physical, psychological, social and spiritual health problems so that the quality of life of the elderly has increased. The satisfaction index of the elderly attending senior school is above 80%.